2003
DOI: 10.1097/01.blo.0000058640.94987.52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Twisting of the Graft in Anterior Cruciate Ligament Reconstruction

Abstract: In an in vitro study on six knees from cadavers, the effect of bone-patellar tendon-bone graft twist on anterior knee laxity was measured at different knee flexion angles. A motion and loading rig was used to prescribe the flexion angle, to restrain axial rotation, and to apply 100 N anterior force to the tibia. Roentgen stereophotogrammetric analysis was used to measure the relative anteroposterior position of the tibia and femur. The tibial bone block was cemented in a cylinder that allowed rotation in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…This AP-error has previously been reported in other in vitro reconstruction studies [7,11,14,[26][27][28]. In agreement with those studies, the reconstructed knees showed the largest APerrors in extension.…”
Section: Discussionsupporting
confidence: 89%
“…This AP-error has previously been reported in other in vitro reconstruction studies [7,11,14,[26][27][28]. In agreement with those studies, the reconstructed knees showed the largest APerrors in extension.…”
Section: Discussionsupporting
confidence: 89%
“…Graft twisting has been thought to increase the stiffness of the graft, but the relevance of graft twisting remains unclear and controversial. 10,23,40,50 Finally, we chose a standard 11-o'clock femoral position because it remains the standard in current practice for transtibial procedures. 31 It is possible that alternate graft orientations could influence our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the effects of graft twist on material properties, isometry, and anterior stability [6,7,17]. In these studies, the graft was twisted by as much as 180".…”
Section: Discussionmentioning
confidence: 99%